Perancangan Dua Jenis Cetakan Bakso Pada Mesin Pencetak Bakso Berbasis Outseal PLC - Bayu Segara; Lela Nurpulaela; Arnisa Stefanie (Jetri : Jurnal Ilmiah Teknik Elektro, 2021)
Various types of culinary delights in various regions of the country of Indonesia, including meatball culinary, are very popular with the Indonesian people because of their distinctive shape and good taste. This meatball molding machine is built for automatic round meatball mold production. The main control on this machine uses PLC outseal control to move the actuators that support the process of producing meatballs on the machine. In the process of printing meatballs on the machine, it is taken from the delay time system on the electric components of the conveyor DC motor and the delay of the dough pressing DC motor on the funnel. The delay of the DC motor for pressing the dough on the funnel is 8 seconds while the delay of the DC conveyor motor is 2.74 seconds so that printing 1 meatball on the machine requires a delay of 10.74 seconds with a meatball production machine capacity of 300 pieces meatball in 1 hour. Beragam jenis kuliner berbagai wilayah negara indonesia termasuk kuliner bakso sangat digemari oleh masyarakat indonesia dikarenakan bentuknya yang khas dan memiliki citarasa yang baik. Mesin pencetak bakso ini dibangun untuk produksi cetak bulat bakso secara otomatis. Kendali utama pada mesin ini menggunakan kendali outseal PLC untuk menggerakkan aktuator yang mendukung untuk proses memproduksi bakso pada mesin. Dalam proses mencetak bakso pada mesin diambil dari sistem waktu delay pada komponen listrik motor DC konveyor dan delay motor DC penekan adonan pada corong.  Delay motor DC penekan adonan  pada corong sebesar 8 detik sedangkan delay motor DC konveyor sebesar 2,74 detik sehingga dalam mencetak 1 bakso pada mesin ialah membutuhkan delay 10,74 detik dengan kapasitas mesin produksi bakso sebanyak 300 buah bakso dalam 1 jam.